Implementation Of The Activity Based Management Method For Cost Efficiency After The Covid 19 Pamdemi At CV. Natural Palembang - Okta Arianingsih; Alwi Alwi; Sri Mardiana (UNIVED Press, 2024)
This study aims to calculate the cost efficiency of carpet production from abaca fiber using the Activity Based Management method and whether the Activity Based Management method used can reduce non-value added costs. This study used qualitative analysis techniques. The types of data used were primary and secondary data. From the analysis conducted at CV Natural Palembang, there were 7 activities which were value-added activities. Weighing, placing the ataka banana fiber in the place where the abaca fiber is separated, removing the colored abaca fiber on the clothesline, selecting the size of the carpet that has been made, checking the quality of the finished goods, sending and storing the finished goods to the warehouse. cost efficiency of 12.2%, CV Natural Palembang has not implemented the demity Based Management (ABM) method in the production process and calculating the costs of its production activities. Companies should apply the Activity Based Management (ABM) method in the production process and calculate the cost of production activities.